Review of Keith Moser, Contemporary French Environmental Thought in the Post-COVID-19 Era (Palgrave Macmillan/Springer Nature, 2022) (ENTHYMEMA, 2023)
Review of Keith Moser, Contemporary French Environmental Thought in the Post-COVID-19 Era (Palgrave Macmillan/Springer Nature, 2022).
Keywords: French Philosophy; Biosemiotics; Animal Studies; Environmental Humanities; Interdisciplinarity